FAKTOR GANGGUAN DAYA INGAT ANAK PENDERITA DOWN SYNDROME BEDA USIA DI SLB NEGERI 1 PADANG (STUDI KASUS PADA PELI DAN SUTAN) - Anita Angraini Lubis (Jurnal Kajian Gender dan Anak, 2020)
The purpose of this study was to describe the factors of memory disorders experienced by children with Down syndrome in different ages at SLB 1 Padang, a case study on Peli and Sutan. The method and technique used in this study were the referencing method for the data collection stage with tapping technique as the basic technique and the advanced technique of proficient involvement (SLC), proficient inactivity (SBLC), note taking, and recording. Articulatory equivalent method for data analysis stage, and formal and informal presentation methods for the presentation phase of data analysis results. This study found that Sutan (S) had difficulties regarding the sequence of counts and alphabets mentioned, while Peli (P) when told to sing, the subject could not sing songs with the correct pronunciation. The lyrics spoken by the subject tend to be wrong and reversed the order. Apart from unclear articulation, and jumping lyrics, it appears that P has memory problems due to the abnormalities he experienced